Recycling of Waste Automotive Engine Oil into a Potential Liquid Fuel via Microwave Pyrolysis - Su Shiung, Lam; Alan D., Russell; Howard A., Chase (ENCON 2013, 2013)
Waste automotive engine oil was treated using a continuous microwave pyrolysis process, with the intention of recovering valuable products from this otherwise difficult to dispose of waste. The resulting pyrolysis gases were condensed into liquid oil; the yield and composition of the recovered oil and remaining incondensable gases were determined. The recovered liquid oil was found to contain substantial concentrations of light aliphatic and aromatic hydrocarbons that could also be used as a chemical feedstock. The recovered gases were found to contain substantial concentrations of light paraffinic hydrocarbons that could potentially be used as a chemical feedstock or a fuel source to power the process. Our results indicate that microwave-heated pyrolysis shows exceptional promise as a means for recycling problematic waste oil.